Usability evaluation survey for identifying design issues in civil flight deck - Aminian, Negin Ozve; Romli, Fairuz Izzuddin; Wiriadidjaja, Surjatin (IOP Publishing, 2015)
Ergonomics assessment for cockpit in civil aircraft is important as the pilots spend most of their time during flight on the seating posture imposed by its design. The improper seat design can cause discomfort and pain, which will disturb the pilot's concentration in flight. From a conducted survey, it is found that there are some issues regarding the current cockpit design. This study aims to highlight potential mismatches between the current cockpit design and the ergonomic design recommendations for anthropometric dimensions and seat design, which could be the roots of the problems faced by the pilots in the cockpit.